PERENCANAAN SUMUR RESAPAN DAN SALURAN DRAINASE PADA PERUMAHAN CHANDRA KIRANA REGENCY KECAMATAN SINGOSARI, KABUPATEN MALANG - Ryan Wahyu Adi Zulfikar, Moch. Suaib Reiza, Suhartono (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
Six hectares Chandra Kirana Regency comprises 223 units. It needs a proper 1854 m drainage system completed with run-off water tanks to avoid it from floods.The objective of the study is to design the drainage system and run-off water tanks able to control the rainwater completed with the implementation cost and time.Site plan, topographic map, and rainfall data were needed to design. Rainfall data from 3 nearby stations: Singosari, Jabung, and Blimbing from 1991-2010 were analyzed to find out the maximum rainfall data and average rainfall regions using Mean Algebra. Log Pearson III was employed to obtain the rainfall, Mononobe method was for the rainfall intensity.The addition of rain water to waste water results in 0,00004 m/sec. cumulative discharge. Based on the result, and 0,5 m diameter culvert rings are designed. 1 m diameter and 2 m deep run-off water tank is of precast concrete. 93 work days implementation time at IDR 1.061.479.450,00.Keywords: design, drainage system, proper, rainwater, water tank